Trends in reference evapotranspiration and associated climate variables over the last 30 years (1984–2014) in the Pampa region of Argentina - D´Andrea, María Florencia (2018)
Agricultural production is sensitive to weather and thus directly affected by climate change. In Argentina, the geographic region known as the “Pampa” is at the heart of agricultural production. In this context, the objective of the present study was to evaluate the presence of long-term trends and abrupt changes in reference evapotranspiration (ETo PM) and associated climate variables in 30 weather stations of the Pampa over the 1984–2014 period. The presence of temporal trends was evaluated using Mann-Kendall’s statistical test, whereas abrupt changes were detected through Pettitt test. Significant upward trends were observed in 80 and 43% of maximum temperature (Tmax) and ETo PM time series, whereas relative humidity (RH) and wind speed (WS), in contrast, presented decreasing trends in 57 and 47% of the locations. Abrupt changes were frequently observed in the years 2000–2003 for Tmax, RH, and ETo PM time series, a period that coincides with the occurrence of flooding events in the region. Weather stations of the Pampa region could be divided into two broad categories based on their trends in ETo PM and influencing climate variables: (A) stations exhibiting a rising trend in ETo PM and a concomitant decreasing trend in RH and (B) stations presenting invariant ETo PM and a decreasing trend in WS. The spatial distribution of the two categories of stations did not exhibit any specific geographic pattern. The information provided herein on modern trends in climate and evaporative demand is essential to the development of climate models and future scenarios necessary to evaluate food security prospects both regionally and globally.